A etnomatemática e os jogos africanos - SOUSA, Simone Maria Leal (2022)
This work aimed to conduct research on the use of African mathematical games from the perspective of ethnomathematics. This research sought to relate African culture through games by means of an analysis of previously published works. The main theoretical and fundamental contribution of this research is its creator Ubiratan D'Ambrósio. The methodology used was based on an integrative bibliographic review in which the authors show the effectiveness of the application of African mathematical games in the classroom as a great tool to help learning. The conclusion is the importance of applying the games as a pedagogical resource that structures thinking and reasoning, in order to solve problems and calculations, with a greater participation of students and teachers, respecting their cultural relations and identity.